Parasitoid Chelonus formosanus Sonan dan tingkat parasitasinya pada ulat grayak (Spodoptera frugiperda Smith) di lahan perkebunan jagung (Zea mays L.) Kecamatan Rasau Jaya, Kalimantan Barat: Parasitoid Chelonus formosanus Sonan and its parasitization level of armyworm (Spodoptera frugiperda Smith) in the corn (Zea mays L.) plantation in Kecamatan Rasau Jaya, Kalimantan Barat - Nurayuda Nurayuda; Kustiati Kustiati; Firman Saputra; Elvi Rusmiyanto Pancaning Wardoyo (Jurnal Entomologi Indonesia, 2026)
The fall armyworm (Spodoptera frugiperda Smith) is an invasive pest that attacks corn crops and has the potential to cause crop failure. One effective strategy is to utilize natural enemies, specifically parasitoids. This study aimed to identify parasitoid species and determine parasitism rates in S. frugiperda across three corn fields in Rasau Jaya I Village, West Kalimantan. Larval samples were collected from 50 plants per field using purposive sampling with a W-shaped scouting pattern, then reared in the laboratory. The results revealed the presence of the parasitoid Chelonus formosanus Sonan with an average parasitism rate of 11.24%, as well as differences in the number of antenna segments compared to previous studies. Chelonus formosanus has the potential to be developed as a biological control agent.